Auditory Pareidolia: Effects of Contextual Priming on Perceptions of Purportedly Paranormal and Ambiguous Auditory Stimuli. Issue 1 (29th August 2014) - Nees, Michael A.; Phillips, Charlotte
Summary Reality television programs that explore purportedly paranormal phenomena with pseudoscientific research approaches have emerged in popular culture. These shows commonly feature electronic voice phenomena (EVP), whereby recording devices capture audio signals that are interpreted as paranormal messages. We compared perceptions for voices in EVP with actual speech, acoustic noise, and degraded speech. Some participants were told that the experiment was about speech intelligibility, whereas others were told that the experiment was about paranormal EVP. The paranormal prime increased the proportion of trials for which participants perceived voices in both EVP stimuli and degraded speech. When a voice was detected, low agreement was found regarding the content of EVP messages. In both priming conditions, participants reported general skepticism in the paranormal. Results are discussed in the context of theoretical perspectives on paranormal events, trait‐versus‐state accounts of paranormal beliefs, and pseudoscientific approaches to research. Copyright © 2014 John Wiley & Sons, Ltd.